Transition to Adulthood and Antiretroviral Adherence Among HIV-Positive Young Black Men Who Have Sex With Men - Hussen, Sophia A. (Am J Public Health, 2015)
Objectives. We conducted a qualitative study of HIV-positive young Black men who have sex with men (YBMSM) to explore their experiences of living with HIV and adhering to antiretroviral medications (ARVs) within the developmental context of their transition to adulthood. Methods. We conducted life history interviews with 20 HIV-positive YBMSM in Atlanta, Georgia, engaged in outpatient HIV care. We addressed these questions: (1) How do YBMSM living with HIV experience the transition to adulthood? and (2) What are the important sociocontextual influences on ARV adherence for YBMSM? Results. Successful transition to adulthood and optimal ARV adherence were inextricably linked. HIV’s detrimental impact on development was moderated by the degree of physical illness at diagnosis. Many participants described resilient trajectories while coping with HIV. Adherence problems occurred primarily among participants who were not meeting their developmental goals. Conclusions. Our findings support the need for early diagnosis and linkage to care, as well as the need to develop holistic, resilience-based interventions focusing on transition to adulthood. These findings have implications for individual clinical outcomes as well as ARV-based prevention efforts among YBMSM.